An investigation of the cleaning performances of femtosecond and nanosecond laser pulses for artificially soiled papers with sizing - Boynukara, Canan Y.; Uguryol, Mehmet; Mavili, Gurcan; Akturk, Selcuk (SPRINGER HEIDELBERG, 2021)
Sizing (ahar) has been used extensively in Turkish-Islamic handwritten documents. In this study, we present comparative experimental results including femtosecond (fs) and nanosecond (ns) pulsed laser cleaning of model paper samples with various types of sizing. The samples were artificially soiled with graphite and graphite-kaolinite mixture. For aging, the samples were exposed to air at 90 C temperature and 50% relative humidity during 16 days. Thickness variations of corn starch sizing were determined, and absorbance and transmittance values of corn, wheat and alum-egg sizing types at UV, VIS and IR wavelengths were measured for comparison. Two different methods and lasers were used for cleaning. In the first method, Yb:Glass fs laser beam (1030 nm wavelength) was focused on the paper surface by using a cylindrical lens (25 mm focal length). Square regions were cleaned through scanning the samples under laser light. Laser fluence was varied in the range of 0.39 - 0.78 J/cm(2). In the second method, a Q-switched Nd:YAG ns laser was operated at fundamental (1064 nm) and second harmonic (532 nm) wavelengths. Laser fluence was varied from 0.24 to 1.24 J/cm(2). Samples were cleaned by means of 1 and 10 laser shots for each fluence. The effectiveness of cleaning was investigated through measurements of color variations, visual and microscopic observations.
Keywords: Laser cleaning; Historical paper; Sizing; Burnished paper; Femtosecond laser; Nanosecond laser; NEAR-UV; Materials Science; Physics